Age, SAPS 3 and female sex are associated with decisions to withdraw or withhold intensive care. Issue 9 (13th June 2019) - Block, Linda; Petzold, Max; Syrous, Alma Nordenskjöld; Lindqvist, Birgitta; Odenstedt Hergès, Helena; Naredi, Silvana
Abstract : Background: Intensive care treat critically ill patients. When intensive care is not considered beneficial for the patient, decisions to withdraw or withhold treatments are made. We aimed to identify independent patient variables that increase the odds for receiving a decision to withdraw or withhold intensive care. Methods: Registry study using data from the Swedish Intensive Care Registry (SIR) 2014‐2016. Age, condition at admission, including co‐morbidities (Simplified Acute Physiology Score version 3, SAPS 3), diagnosis, sex, and decisions on treatment limitations were extracted. Patient data were divided into a full care (FC) group, and a withhold or withdraw (WW) treatment group. Results: Of all 97 095 cases, 47.1% were 61‐80 years old, 41.9% were women and 58.1% men. 14 996 (15.4%) were allocated to the WW group and 82 149 (84.6%) to the FC group. The WW group, compared with the FC group, was older ( P < 0.001), had higher SAPS 3 ( P < 0.001) and were predominantly female ( P < 0.001). Compared to patients 16‐20 years old, patients >81 years old had 11 times higher odds of being allocated to the WW group. Higher SAPS 3 (continuous) increased the odds of being allocated to the WW group by odds ratio [OR] 1.085, (CI 1.084‐1.087). Female sex increased the odds of being allocated to the WW group by 18% (1.18; CI 1.13‐ 1.23). Conclusion: Older age, higher SAPS 3 at admission and female sex were found to be independent variables that increased the odds to receive a decision to withdraw or withhold intensive care.